The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/antibiotics9050222
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life of Patients with Mandibular Third Molars and Mild Pericoronitis. A Comparison between Two Different Treatments: Extraction or Periodontal Approach

Abstract: Background: The extraction of the mandibular third molar is one of the most frequent intervention in oral surgery. A common indication for wisdom tooth extraction is represented by pericoronitis, which can determine discomfort and pain in patients. The present study aimed to evaluate the impact of patients’ quality of life by comparing a surgical approach with a periodontal approach. Methods: We evaluated 82 patients diagnosed with pericoronitis that occurred at the third molar site. In total, 41 of them recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
1
4
0
1
Order By: Relevance
“…Most published studies evaluated the OHIP-14 post-operatively following extraction [ 31 ]. However, in line with our findings of baseline global OHIP-14 scores of 22.5 ± 8.3, Passarelli et al reported that the mean baseline OHIP-14 scores of patients who underwent third molar surgery were 19.7 ± 9.9 [ 32 ]. In the present study, worse OHIP-14 scores were positively associated with worse health-related behaviors such as performing physical activity less than once a week, higher plaque scores, and specific characteristics of the third molar teeth, such as pericoronitis and radiolucency around third molars.…”
Section: Discussionsupporting
confidence: 92%
“…Most published studies evaluated the OHIP-14 post-operatively following extraction [ 31 ]. However, in line with our findings of baseline global OHIP-14 scores of 22.5 ± 8.3, Passarelli et al reported that the mean baseline OHIP-14 scores of patients who underwent third molar surgery were 19.7 ± 9.9 [ 32 ]. In the present study, worse OHIP-14 scores were positively associated with worse health-related behaviors such as performing physical activity less than once a week, higher plaque scores, and specific characteristics of the third molar teeth, such as pericoronitis and radiolucency around third molars.…”
Section: Discussionsupporting
confidence: 92%
“…A complete evaluation of post-operative conditions after third molar surgery is fundamental to detect eventual inflammatory complications, such as pain, swelling, trismus, infection, and alveolar osteitis, all implying a relevant negative impact on everyday quality of life of patients [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some authors have also proved a correlation between the inclusion and the number of roots of the third molar, the ramus and the alveolar bone height [2,9]. Indeed, there is greater probability of inclusion in cases where the tooth has more than two roots, the ramus has shown a lesser development or the alveolar nerve is higher [10]. On the whole, no differences between men and women regarding impaction are present, but it was demonstrated that facial characteristic and inclination of eruption can influence impaction [11,12].…”
Section: Introductionmentioning
confidence: 98%